Sleep Apnea - Recent Updates 2017
DOI: 10.5772/66570
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Artificial Neural Networks in the Diagnosis and Treatment of Sleep Apnea-Hypopnea Syndrome

Abstract: Sleep apnea-hypopnea syndrome (SAHS) is a chronic and highly prevalent disease considered a major health problem in industrialized countries. The gold standard diagnostic methodology is in-laboratory nocturnal polysomnography (PSG), which is complex, costly, and time consuming. In order to overcome these limitations, novel and simplified diagnostic alternatives are demanded. Sleep scientists carried out an exhaustive research during the last decades focused on the design of automated expert systems derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 99 publications
(108 reference statements)
0
8
0
12
Order By: Relevance
“…In the context of automated signal processing and pattern recognition, the following stages are essential to compose and optimize a high-performance as well as generalizable model [24]:…”
Section: Advanced Signal Processing and Automated Pattern Recognitionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the context of automated signal processing and pattern recognition, the following stages are essential to compose and optimize a high-performance as well as generalizable model [24]:…”
Section: Advanced Signal Processing and Automated Pattern Recognitionmentioning
confidence: 99%
“…Different studies reported significantly decreased CTM values, i.e., higher variability, in SpO2 recordings from OSAS patients due to the recurrent desaturations, both in adults [29] and in children [15,24]. Similarly, the Lempel & Ziv complexity (LZC) is a nonlinear measure of complexity linked with the number of new patterns and their repetition along the signal.…”
Section: Advanced Signal Processing and Automated Pattern Recognitionmentioning
confidence: 99%
See 3 more Smart Citations